Effect of course length and corridor width on the 2-minute walk test performance in geriatric patients. (February 2017) - Lindemann, Ulrich; Beck, Luisa; Becker, Clemens
Objective: To evaluate the effect of course length and corridor width on 2-minute walk test results in older adults. Design: Cross-sectional and experimental study with different test conditions. Setting: Geriatric rehabilitation clinic. Subjects: A total of 21 patients (median age 81 years). Main measures: Patients walked two minutes on a 20 m and 40 m course with a 2 m or 1 m corridor width and on a continuous course without any turning in a corridor of 2 m width, five walks in total. The distance traveled within the 2 minutes was recorded. Results: Compared with the 20 m course length, median walking distances measured by the 2-minute walk test in a walk way 2 m broad were better on the continuous corridor without any turn (136.9 m vs. 129.3 m, p  = 0.002) and on the 40 m course (131.8 m vs. 129.3 m, p  = 0.003). Walking distance on a 20 m course length was longer in a corridor of 2 m width compared with the 1 m corridor width (129.3 m vs. 119.2 m, p  = 0.005). The walking distance was not affected by corridor width on the 40 m course length. Conclusions: Performance of elderly patients on the 2-minute walk test is influenced by the width of the corridor and the length of the course used.